Conceptions About Electrical Circuits Of English And French Pupils From Nova Scotia In Canada: English And French Conceptions On Electric Circuits - Métioui, Abdeljalil; Trudel, Louis (EDU REVIEW. International Education and Learning Review / Revista Internacional de Educación y Aprendizaje, 2020)
This research study was designed to identify the conceptual understandings of 89 students from the region of Clare in French-language public schools and 105 students from the Argyle region in French immersion public schools in Canada on the operation of simple electrical circuits. To this end, they completed a pencil-and-paper questionnaire of sixty minutes in duration. The analyses of the data show clearly the preponderance of erroneous understandings by students related to the concepts of current and voltage among other related concepts identified in the international review of the literature. Thus, despite the cultural and language differences, their conceptual understandings related to the simple electrical circuit are similar. A conclusion and didactical impact are included.